Targeted metabolome and transcriptome analyses reveal changes in gibberellin and related cell wall-acting enzyme-encoding genes during stipe elongation in Flammulina filiformis - Li, Hui; Yao, Sen; Xia, Weiwei; Ma, Xinbin; Shi, Lei; Ju, Huimin; Li, Ziyan; Zhong, Yingli; Xie, Baogui; Tao, Yongxin (Frontiers in Microbiology, 2023)
Flammulina filiformis, a typical agaric, is a widely cultivated and consumed edible mushroom. Its stipe elongation (the main edible part) is closely related to its yield and commercial traits, however, the endogenous hormones during stipe elongation and their regulatory mechanisms are not well understood. Gibberellin(GA) plays an important role in the regulation of plant growth, but little was reported in macro fungi yet. In this study, we firstly treated F. filiformis stipe in the young stage with PBZ (inhibitor of GA), and found that PBZ could significantly inhibit the elongation of stipe. Then, we performed the GA targeted metabolome and transcriptome detection for the stipe at both the young and elongation stages. Total 13 types of GAs were detected in F. filiformis, ten of them including GA3,GA4,GA8,GA14,GA19,GA20,GA24,GA34,GA44,and GA53, were significantly decreased, and three (GA5,GA9,and GA29) were significantly increased during the stipe elongation. Transcriptome results showed that the genes in the terpenoid backbone biosynthesis pathway showed the varying expression patterns: HMGS, HMGR, GPS and FPPS were significantly up-regulated, while CPS/KS had no significant difference in the transcription level during stipe elongation. In total 37 P450 genes were annotated to be involved in GAs biosynthesis, eight of them were up-regulated, twelve were down-regulated, and the rest were not differentially expressed. In addition, four types of the differentially expressed genes involved in the stipe elongation were also identified including six signal transduction genes, five cell cycle controlling genes, twelve cell wall-related enzymes and six transcription factors. The results identified the types and content of GAs and the expression pattern of their synthesis pathways during the elongation of the F. filiformis, and also revealed the molecular mechanisms by which the GAs may affect the synthesis of cell wall components and cell cycle of the stipe through the downstream action of cell wall-related enzymes, transcription factors, signal transduction and cell cycle cotrolling, thus regulating the stipe elongation of the F. filiformis. It is helpful to understand the roles of GAs in the stipe development of the mushroom, and lays the foundation for the rational regulation of the stipe length of the agaric mushroom in production.